FAKTOR-FAKTOR YANG MEMPENGARUHI KONSERVATISME AKUNTANSI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2016 - Diyan Kurnia Puspita Saputri, 14.05.52.0158; Nurhayati, Ida (Students' Journal of Accounting and Banking, 2019)
This study examines and analyze the effects of institutional ownership structures, managerial ownership structures, public ownership structures, firm size, debt convenant (leverage), litigation risk to accounting conservatism. The population in tihs study is a manufacturing company listed on the Bursa Efek Indonesia period from 2014-2016. The sampling method used purposive sampling. The relationship and between variable is described by using multiple regression analysis methods. The results showes that the institutional ownership structures has a significant negative effect on accounting conservatism, managerial ownership structures has a significant negative effect on accounting conservatism, public ownership structures has a significant negative effect on accounting conservatism, debt covenant (leverage) has significant positive effect on accounting conservatism, litigation risk has positive effect on accounting conservatism.